The use of Cilostazol in Diabetic Patients - Konstantinos Spanos; Athanasios D Giannoukas (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2016)
The International Diabetes Federation (IDF) reported that the global prevalence of diabetes (DM) in adults was 8.3% in 2013 expecting to rise beyond 592 million by 2035 with a 10.1% global prevalence [1]. Guidelines have been published for the treatment of this major disease and its complications [2,3]. Recently, cilostazol has been proposed for the treatment of diabetic patients and their complications. Cilostazol is a selective inhibitor of phosphodiesterase type 3 that appears to have both antiplatelet and anti-proliferative effects [4]. Cilostazol inhibits platelet aggregation in response to ADP, epinephrine, collagen and arachidonic acid, and suppresses the production of platelet derived endothelial cell growth factor [4].